One-pot synthesis of nanostructured carbon materials from carbon dioxide via electrolysis in molten carbonate salts. (September 2016) - Wu, Hongjun; Li, Zhida; Ji, Deqiang; Liu, Yue; Li, Lili; Yuan, Dandan; Zhang, Zhonghai; Ren, Jiawen; Lefler, Matthew; Wang, Baohui; Licht, Stuart
Abstract: As the primary culprit of greenhouse effect, carbon dioxide has garnered global attention, and the technologies currently being developed to reduce the emission of CO2 vary widely. In this study, CO2 was electrochemically reduced in various molten mixtures of LiNaK carbonates to carbon nanomaterials. By regulating the electrolysis current density, electrolyte, and electrolytic temperature, the carbon products had different morphologies of honeycomb-like and nanotubular structures. A transition from a honeycomb/platelet to nanomaterial carbon morphology was observed to occur at ∼600 °C with increase in temperature. The observation of nanostructures is consistent with a higher diversity of structures possible with enhanced rearrangement kinetics that can occur at higher temperature. A high yield of a carbon nanotube (CNT) was not observed from a LiNaK electrolyte, no CNTs are formed from a NaK carbonate electrolyte, but a high yield is observed from pure Li, or mixed LiNa or mixed LiBa carbonate electrolytes, and the carbon nanotube product diameter is observed to increase with increasing electrolysis time.